Intravenous glutathione for skin lightening: Inadequate safety data - Davids, Lester M; Van Wyk, Jennifer C; Khumalo, Nonhlanhla P (South African medical journal, 2016)
Glutathione (GSH) is the most abundant naturally occurring non-protein thiol that protects mammalian cells from oxidative stress. Intravenous (IV) GSH for skin lightening is advertised by clinics in South Africa and internationally online, yet to date no published review on the subject exists. Methods. We conducted a MEDLINE search (to 30 September 2015) of GSH use for skin lightening and of all indications in medicine, to evaluate its safety. Results. Two controlled clinical trials (GSH capsules: 60 patients; 2% glutathione disulphide lotion: 30 patients) and a case series (GSH lozenges: 30 patients) reported a significantly decreased melanin index. A case series (GSH soap: 15 patients) reported skin lightening based on photography. Two systematic reviews of IV GSH for preventing chemo-induced toxicity and a third review of adjuvant therapy for Parkinson's disease altogether included 10 trials. Most trials reported either no or minimal GSH adverse effects, but all had treatment durations of a few doses (IV) or 4 -12 weeks. No study reported long-term IV GSH use. Conclusion. In spite of widespread reported use, there are no studies of IV GSH use for skin lightening or of its safety for chronic use (for any indication). The switch from brown to red melanin production may increase the risk of sun-induced skin cancers in previously protected individuals. Regulatory assessment of systemic GSH administration for cosmetic use by the Medicines Control Council seems urgently warranted to protect consumers from potential side-effects and from complications of IV infusions. This is especially concerning because of reports of GSH bought online. Effective topical GSH may be useful for hyperpigmented skin disorders, but this requires scientific scrutiny. The debate on the merits of cosmetic skin lightening is best handled by multidisciplinary teams.